Do social constructivists tell us something real about economics? - Kurkowski, Bartosz Paweł (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2019)
Social constructivists use to say that economists cannot study objective reality, absolute truth does not exist, and economic knowledge is being constructed, not discovered and it depends on temporary culture. Realists notice and admit social conditions which may affect economic theories and unrealistic assumptions of models, but they claim that these models describe the real world, at least to some extent. The notions of truth and reality are crucial in both of these concepts. In this papar they are analysed based on Hilary Putnam theory developed by Adam Grobler.